The interactive effects of zinc source and feed grade medication on weanling pig growth performance - J C Woodworth; J T Sawyer; K A Maxwell; T M Fakler; Michael D Tokach; Jim L Nelssen; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1999)
Two hundred eight-eight weanling pigs (initially 12.31bs and 18 d of age) were used in a 27-d growth assay to determine the interactive effects of Zn source and feed grade medication on growth performance. Experimental treatments were arranged in a 2 x 3 factorial with main effects of medication (none or 50 g/ton of carbadox) and Zn source (none, 250 ppm of Zn from a Zn amino acid complex, or 3,000 ppm of Zn from ZnO). The results suggest that dietary Zn improved growth performance primarily from d Â°to 14 and feed grade medication improved growth performance from d 14 to 27. Pigs fed diets containing ZnO had better growth performance than pigs fed diets containing no additional Zn, and pigs fed diets containing ZnAA had intermediate responses.; Swine Day, Manhattan, KS, November 18, 1999
Keywords: Swine day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 841; Swine; Early-weaned pigs; Growth; Zinc; Medication